Is the integration of world asset markets necessarily beneficial in the presence of monetary shocks? - Cédric Tille (Federal Reserve Bank of New York, 2000)
This paper evaluates the consequences of the integration of international asset markets when goods markets are characterized by price rigidities. Using an open economy general equilibrium model with volatility in the money markets, we show that such an integration is not universally beneficial. The country with the more volatile shocks will benefit whereas the country where the volatility of shocks is moderate will suffer. The welfare effects reflect changes in the terms of trade that occur because forward looking price setters adjust to the changes in exchange rate volatility brought about by the integration of international asset markets.
Keywords: F33; F36; F41; F42; 330; international risk sharing; terms of trade; Internationaler Finanzmarkt; Marktintegration; Unvollkommener Markt; Güter; Preisrigidität; Geldmenge; Schock; Zwei-Länder-Modell; Theorie